SUSTAINABLE DEVELOPMENT AND THE ROLE OF THE CHARTERED ACCOUNTANT IN IMPLEMENTING THE UNIFIED ACCOUNTING SYSTEM IN IRAQ - Anwer Abed Shahoobe (Scholars Digest Publishing, 2024)
Achieving profits is regarded as one of the most important goals that profit-oriented economic units seek, but achieving this goal may be governed by societal restrictions. So, this corresponds to a social and environmental responsibility. Economic stagnation turns the significance of accountancy within the concept of proprietary, which is crystallized to magnify the self-interest of artisans in the companies. So, it is necessary to balance public and private interests to achieve sustainable development and not be affected by subsequent generations. Sustainable development in Iraq represents a general goal for all citizens of Iraqi society because achieving this goal means transferring the reality of Iraq from one case to another. Our research came to define and evaluate the role of the chartered accountant in sustainable development. The importance of this role is that this tool (The chartered accountant) provides the required healthy bases to arrange plans and programs to develop in all economic sectors. The choice of Iraq occurs as it is going through a transitional phase in all fields, and at the forefront of these changes is turning the general approach of the Iraqi economy from a planned and central economy to a market economy by implementing the unified accounting system in Iraq. And its amendments are considered one of the most essential bases necessary to keep pace with these changes.
Keywords: Accounting, Sustainable Development, Unified Accounting, Iraqi economy.